Radical reflexivity, experimental ontology and RRI - Robert Braun (Journal of Responsible Innovation)
RRI does not challenge what this paper calls ‘lyseology’: mobilizing science to convince policy makers and the public that the present possesses some form of lack that should be addressed with a new technology. For a sustained critique of technological fixes as solutions a more radical shift from the persistent old view of a static outside world is required. This entails a process-based understanding of reality and specific consequences thereof for practice. To do so the paper offers an analysis of in what manner current RRI discourse builds on old subject-object ontologies and relies on an outdated worldview. The paper suggests possible pathways of conceiving of research and innovation otherwise: RRI should reorient towards the ontology turn, learn from ethnomethodology and radical reflexivity, as well as from the politics of material participation. This paper proposes that research and innovation should engage with quantum theory inspired alternative worldviews.